Features of quality of life formation in children with visual impairments - L. I. Denysiuk (Patologìâ)
The relevance of the study is determined by the importance of complete healthy visual perception for quality of life and productivity in childhood. Prognostic calculations by international experts indicate increasing trends in the prevalence of ophthalmic pathology, with projections suggesting that by 2050, practically one-third of the world’s population will have visual impairments, the vast majority of which are diagnosed in childhood.